Search for baryon and lepton number violating decays of the tau lepton - Godang, R; Kinoshita, K; Lai, I; Pomianowski, P; Schrenk, S; Bonvicini, G; Cinabro, D; Greene, R; Perera, L; Zhou, G; Chan, S; Eigen, G; et al. (1999)
We have searched for five decay modes of the τ lepton that simultaneously violate lepton and baryon number: τ-→p̄γ, τ-→p̄π0, τ-→p̄η, τ-→p̄2π0, and τ-→p̄π0η. The data used in the search were collected with the CLEO II detector at the Cornell Electron Storage Ring. The integrated luminosity of the data sample is 4.7 fb-1, corresponding to the production of 4.3 × 106 τ+τ- events. No evidence is found for any of the decays, resulting in much improved upper limits on the branching fractions for the two-body decays and first upper limits for the three-body decays. ©1999 The American Physical Society.